Role of pulse oximetry in screening newborns for congenital heart disease at 1 hour and 24 hours after birth - Siva, Padmapriya; Senthilvelan, Bharathi; Gopalakrishnan, Harini; Subramanian, Sellaraman (International Journal of Contemporary Pediatrics, 2016)
Background: The incidence of congenital heart disease is 8-10 /1000 live birth in different parts of the world. Early detection of major critical congenital heart defects might improve the outcome of new-born babies. Echocardiography is mainly used as diagnostic tool rather than screening tool due to cost effectiveness. Thus pulse oximetry, non-invasive easy to perform stays as main screening tool for diagnosis of critical congenital heart disease in newborn. Methods: Prospective study conducted in Neonatal unit in Chennai Medical College Hospital & research centre over a period of one year. A total of 430 asymptomatic newborn delivered were screened with pulse oximetry at 1 hour and 24 hours after birth. All positive newborns were screened with echocardiography. Results: Out of 430 newborns screened, 5 newborns had saturation <95% at 1 hour. Echocardiography was done in all 5 babies, out of which 3 revealed hypoplastic left heart syndrome, 1 had transposition of great arteries and 1 had truncus arteriosus. The sensitivity, specificity, positive predictive value and negative predictive value of the pulse oximetry in screening of heart disease in newborn was 55.55%,100%, 100% & 99.01% respectively. Conclusions: Pulse oximetry will detect more infants in settings with a lower prenatal diagnosis rate. Pulse oximetry helps to diagnose critical congenital heart disease even at 1 hour of life which helps in early intervention and thereby improves outcome.